2020
DOI: 10.1177/0146167220972245
|View full text |Cite
|
Sign up to set email alerts
|

Trustworthiness and Ideological Similarity (But Not Ideology) Promote Empathy

Abstract: The current highly polarized U.S. political culture impedes people’s ability to live and work together effectively. Here we examine one factor that may play a role: selective empathy based on shared political ideology. Across seven studies ( N = 3,476), participants read about a hypothetical politician and his political ideology, trustworthiness, or both. Participants reported their empathy for the politician after learning he was fined (Studies 1–6) or injured (Study 7). When trustworthiness alone was manipul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Previous work has demonstrated the influence of ideological salience on intergroup relations and the importance of understanding cognitive processes within larger ideological contexts [ 44 46 ]. Opposing political ideologies have also been shown to modulate empathic responses, with greater empathy reported between individuals with similar political ideologies [ 47 , 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has demonstrated the influence of ideological salience on intergroup relations and the importance of understanding cognitive processes within larger ideological contexts [ 44 46 ]. Opposing political ideologies have also been shown to modulate empathic responses, with greater empathy reported between individuals with similar political ideologies [ 47 , 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, not all prior studies have supported the idea of ideological asymmetry. For instance, one study ( 17 ) found no difference between liberals and conservatives in the empathy they felt toward their political opponents. Further, although aggression is indeed included in classic conceptualizations of RWA, there have been suggestions that RWA is not necessarily a unidimensional construct and that relations between its subdimensions and social outcomes may be more complex ( 18 ).…”
Section: Left-wing Versus Right-wing Extremismmentioning
confidence: 99%
“…For instance, individuals are motivated to feel more empathy toward people who share their political views (Hasson et al, 2018). Likemindedness has been argued to be a stand-alone reason for feeling empathy toward an individual (Stevens et al, 2020).…”
Section: Social Identity Theory Approach To Bystander Reactionsmentioning
confidence: 99%